Mechanical stimulation in Brachypodium distachyon: Implications for fitness, productivity, and cell wall properties. (17th February 2020) - Gladala‐Kostarz, Agnieszka; Doonan, John H.; Bosch, Maurice
Abstract: Mechanical stimulation, including exposure to wind, is a common environmental variable for plants. However, knowledge about the morphogenetic response of the grasses (Poaceae) to mechanical stimulation and impact on relevant agronomic traits is very limited. Two natural accessions of Brachypodium distachyon were exposed to wind and mechanical treatments. We surveyed a wide range of stem‐related traits to determine the effect of the two treatments on plant growth, development, and stem biomass properties. Both treatments induced significant quantitative changes across multiple scales, from the whole plant down to cellular level. The two treatments resulted in shorter stems, reduced biomass, increased tissue rigidity, delayed flowering, and reduced seed yield in both accessions. Among changes in cell wall‐related features, a substantial increase in lignin content and pectin methylesterase activity was most notable. Mechanical stimulation also reduced the enzymatic sugar release from the cell wall, thus increasing biomass recalcitrance. Notably, treatments had a distinct and opposite effect on vascular bundle area in the two accessions, suggesting genetic variation in modulating these responses to mechanical stimulation. Our findings highlight that exposure of grasses to mechanical stimulation is a relevant environmental factor affecting multiple traits important for their utilization in food, feed, and bioenergy applications. Abstract : We show that mechanical stimulation of the grass model Brachypodium distachyon induces a range of changes, several varying quantitatively between accessions, from the cellular and tissue level to whole plant morphology with important implications for fitness, productivity, and quality‐related traits.